PENAPISAN DAN KARAKTERISASI PARSIAL SENYAWA ANTIMIKROBA DARI SIPUT BAKAU DAN PROFIL KROMATOGRAFI LAPIS TIPIS FRAKSI AKTIF - Alimuddin Ali; Yusminah Hala; Darminto Darminto (The East Java Biological Society, 2006)
Mangrove snail is one of the animal medicines used againts bacterial infection, however, the scientific basic of the activity still void. The aim of this research were to investigate the antimicrobial effect of mangrove snail as the primary step to identify an antimicrobial activity and find out substances responsible to this activity. The study was conducted by collecting 4 snail samples. Extract were made be maceration of methanol and followed by chloroform and n-butanol partision, respectively. Antimicrobial activity has been done using Salmonella typhii, Staphylococcus aureus, Escherichia coli and fungi Candida albicans. The result showed that these mangrove snail capable inhibit bacterial growth either Gram positive or negative, but can not inhibition fungi. Methanol extract of Terebralia sulcata showed inhibition zone has the Rf 0.27, whereas chloroform fractions of Charonia sp. has 6 spots by bioautographic. Two out of six spots showed inhibition zone with Rf 0.16 and Rf 0.4. Methanol extract of N. birmanica has inhibit with Rf 0.56. One spots with Rf 0.42 unclear as inhibition zone suggested negative. Then the methanol extract of Telescopium telescopium with Rf 0.34 showing inhibition zone.